(untitled) (Ustozlar uchun, 2026)
This article examines the role of information and communication technologies in assessing language skills in teaching and learning English as a Foreign Language. It analyzes how digital tools influence the assessment of listening, reading, writing, speaking, vocabulary and grammar. The paper highlights the strengths and weaknesses of using ICT based assessment showing that they provide immediate feedback, objective scoring, learner autonomy and flexible access to various test formats. The study concludes that integrating ICT based assessment tools into regular English instruction significantly enhances the accuracy of skill evaluation and learner motivation.